Unrealistic optimism and the ethics of phase I cancer research. Issue 6 (31st October 2012) - Crites, Joshua; Kodish, Eric
Abstract : One of the most pressing ethical challenges facing phase I cancer research centres is the process of informed consent. Historically, most scholarship has been devoted to redressing therapeutic misconception, that is, the conflation of the nature and goals of research with those of therapy. While therapeutic misconception continues to be a major ethical concern, recent scholarship has begun to recognise that the informed consent process is more complex than merely a transfer of information and therefore cannot be evaluated only according to how well an individual understands such information. Other components of decision-making operate independently of understanding and yet still may compromise the quality of informed consent. Notable among these components is unrealistic optimism, an event-specific belief that one has a better chance of receiving benefit than others similarly situated. In this article, we consider responses to interviews with parents who had recently completed an informed consent conference for enrolling their child in a phase I cancer clinical trial to examine how this influence manifests and how investigators might address it during informed consent.